Pengaruh Literasi Keuangan, Pengetahuan Keuangan Dan Sikap Keuangan Terhadap Perilaku Manajemen Keuangan Pada Pelaku Usaha UMKM Fashion Di Kabupaten Malang - Fanisa Kris Dayanti; Jeni Susyanti; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis purpose of this research is Financial Literacy, financial knowledge and Financial Attitudes on Financial Management Behavior in fashion MSME entrepreneurs in Malang Regency. This research is a quantitative study with data collection techniques using a questionnaire. The sample in this study amounted to 40 respondents. The sampling technique used was the accidental sampling method. Primary data processing uses Statistical Package for Social Science (SPSS) analysis techniques with multiple regression analysis methods. The results of this study indicate that simultaneous variables of financial liabilities, financial knowledge and financial attitudes have a positive and significant effect on financial management behavior. Partially, each independent variable has a positive and significant effect on financial management behavior. Keyword : financial literacy, financial knowledge, financial attitudes and financial management behavior